A model for the growth and development of wave‐dominated deltas fed by small mountainous rivers: Insights from the Elwha River delta, Washington. Issue 5 (5th March 2020) - Zurbuchen, Julie; Simms, Alexander R.; Warrick, Jonathan A.; Miller, Ian M.; Ritchie, Andrew
Abstract: Observations from ground‐penetrating radar, sediment cores, elevation surveys and aerial imagery are used to understand the development of the Elwha River delta in north‐western Washington, USA, which prograded as a result of two dam removals in late 2011. Swash‐bar, foreshore and swale depositional elements are recognized within ground‐penetrating radar profiles and sediment cores. A model for the growth and development of small mountainous river wave‐dominated deltas is proposed based on observation of both the fluvial and deltaic settings. If enough sediment is available in the fluvial system, mouth‐bars form after higher than average river discharge events, creating a large platform seaward of the subaqueous delta plain. Swash‐bars form concurrently or within a month of mouth‐bar deposition as a result of wave action. Fair‐weather waves drive swash‐bar migration landward and in the direction of littoral drift. The signature of swash‐bar welding to the shoreline is landward‐dipping reflections, as a result of overwash processes and slipface migration. However, most swash‐bars are eroded by the river mouth, as only 10 of the 37 swash‐bars that formed between August 2011 and July 2016 survived within the Elwha River delta. The swash‐bars that do survive either amalgamate onto the shoreline or an earlier deposited swash‐bar, forming a single larger barrier at the delta front. In asymmetrical deltas, the signature of swash‐bar welding is more likely to be preserved on the downdrift side of the delta, where formation is more likely and accommodation behind newer swash‐bars preserves older deposits. On small mountainous river deltas, welded swash‐bars may be more indicative of a large sediment pulse to the system, rather than large hydrological events.